Bathymetric Mapping Techniques for Shallow Marine Waters Using Satellite Image Data at the Oceanographic Research Center (P2O)-LIPI in Jakarta - Nabila Afifah Azuga; Fharisa Nabila Rizvi; Okta Rizal Karsih; Ronal Kurniawan (Tropical Marine Environmental Sciences, 2026)
An application is a subclass of computer software that utilizes the computer’s capabilities directly to perform a task desired by the user. The purpose of this study was to investigate bathymetric mapping techniques using Planet Scope satellite imagery and methods for processing data collected in the field. The research was conducted from January to February 2019 at the Remote Sensing Laboratory of the Oceanography Research Center, Indonesian Institute of Sciences (P2O-LIPI), East Ancol, North Jakarta. The methods used during this internship included active participation and literature review. To this context, the author processed satellite image data and analyzed the data using a laptop equipped with ArcGIS 10.5, Microsoft Excel, and ENVI 5.3. The results from data processed manually to determine absolute depth exhibited a higher level of accuracy ompared to data processed automatically